Nanotechnology: An Overview Based on Indicators and Statistics - Palmberg, Christopher (OECD Science, Technology and Industry Working Papers, 2009)
Nanotechnology is commonly considered to offer considerable promise extending from business opportunities throughout various industries to broader socio-economic benefits, especially in the context of pressing global challenges such as those related to energy, health care, clean water and climate change. Governments around the world have invested heavily in R&D in this field and companies are also becoming increasingly engaged. Despite this promise, investments and company involvement in nanotechnology developments are still poorly monitored. The objective of this report is to provide a comprehensive overview of these developments through a systematic and critical analysis of available indicators and statistics, while acknowledging that there is a need for further work to both broaden the range of, and develop further, nanotechnology metrics